Mappadendang Tradition in Efforts to Preserve The Environment in Parepare Communities of Indonesia - Zahrawati, Fawziah; Andriani, Andriani; Natasya, Natasya; Syarah, Indri; Yuniar, Yuniar (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
This study aims to examine the existence of the Mappadendang tradition of the Parepare community in Indonesia, implementing the Mappadendang tradition, and the Mappadendang tradition related to environmental conservation efforts. A qualitative approach is used to answer the research objectives. This research was conducted in Watang Bacukiki, Parepare City, Indonesia. Informants in this study are the people who live around the research location and take part in carrying out the Mappadendang tradition. The data collection techniques are interviews and documentation. After the data is collected, the data is analyzed. This study found that the Mappadendang tradition has been implemented since the community has been familiar with agriculture and the tradition still exists today. Implementing Mappadendang tradition includes rice mashing activities, dances, and eating together. The Mappadendang tradition cannot be separated from efforts to preserve the environment. This can be seen from the activities of cleaning the environment together and the stipulation of rules not to litter and to carry out activities that do not damage the environment. From the findings of this study, it can be concluded that the Mappadendang tradition, as a tradition passed down from generation to generation, must be preserved because implementing the tradition is closely related to environmental conservation efforts.